(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Background. The main cause for the development of proliferative diabetic retinopathy (DRP) is the absence of capillary perfusion, resulting in the initiation of retinal neovascularization. In ischemia reperfusion injury of the retina, the plasminogen activator inhibitor 1 (PAI-1), inflammatory mediators, cytokines, adhesion factors activated in the metabolic syndrome (MS) may be involved. Therefore, there is a necessity to evaluate the role of PAI-1 in the initiation and progression of DRP in MS. Purpose. To study the activity of PAI-1 in blood of patients with the metabolic syndrome (MS) depending on a stage of diabetic retinopathy (DRP) and in relation with a level of circulating interleukin-8 (IL-8) and blood fibrinogen. Material and Methods. Studies were carried out in 64 patients (95 eyes) with MS and DRP, comparable in sex, age and duration of type 2 diabetes mellitus (T2DM), which were divided into 3 groups depending on a stage of DRP. The control group consisted of 23 individuals of both sexes with obesity without T2DM. The activity of PAI-1 and the concentration of circulating IL-8 in blood were determined by enzyme immunoassay; fibrinogen was assessed by the clotting method. Statistical analysis included single-factor analysis of variance (ANOVA) and regression analysis. Results. It was shown that only in the case of conditional combination of DRP stages II and III in one stage, the activity of PAI-1 was statistically significantly lower in comparison with the control group ((21.3 ± 2.8 U / ml (95% CI 17.3-25, 3) vs 12.0 ± 3.3 U / ml (95% CI 7.43-16.6), p < 0.05)), which did not occur in DRP stage (p> 0.05). In the group of patients with T2DM, regardless a stage of DRP, the level of PAI-1 activity was positively associated with circulating IL-8 concentration (r = 0.43, R2 = 18.6 %, N = 54, p = 0.001). Also, an inverse linear dependence of blood fibrinogen concentration on the PAI-1 activity was revealed (r = -0.36, R2 = 13.6%, N = 55, p = 0.005). Conclusion. Patients with DRP and MS had significantly decreased PAI-1 at DRP stages II and III compared to non-diabetic obese patients (р<0.05) unlike the patients with DPR stage I (p>0.05); a strong significant positive association between PAI-1 and circulating IL-8 (p=0.001) and a significant negative linear relationship between blood fibrinogen concentration and PAI-1 (p=0.005) were revealed.